BiFeO3 nanorings synthesized via AAO template-assisted pulsed laser deposition and ion beam etching. Issue 65 (23rd August 2017) - Tian, Guo; Chen, Deyang; Yao, Junxiang; Luo, Qiuyuan; Fan, Zhen; Zeng, Min; Zhang, Zhang; Dai, Jiyan; Gao, Xingsen; Liu, Jun-Ming
Abstract : Well-ordered BiFeO3 nanorings with epitaxial structure, strong ferroelectricity and polarization reversal have been fabricated using this novel and facile method. Abstract : We propose a novel and facile method to fabricate epitaxial ferroelectric BiFeO3 (BFO) nanorings using anodized alumina (AAO) template-assisted PLD and ion-beam etching. The morphology and dimensions of these nanorings are revealed by atomic force microscopy (AFM) and confirmed by transmission electron microscopy (TEM). The typical dimensions of the BFO nanorings are 12 nm inner diameter with 30 nm wall thickness and heights of around 10 nm. The X-ray diffraction (XRD), reciprocal space mapping (RSM) and TEM data demonstrate the epitaxial structure of these nanorings. Moreover, the ferroelectric properties are investigated by piezoresponse force microscopy (PFM), showing the polarization reversal behaviors of the isolated BFO nanorings, which have great potential applications for high-density non-volatile memory devices. In addition, this novel method could also be extended to other material systems (such as BaTiO3, ZnO and Au). Furthermore, the fabrication of high quality nanoring structures may open a pathway to explore related emerging physical phenomena ( e.g., ferroelectric vortices).